Analysis of various reliability parameters for rice industry. (May 2020) - Kumar, P; Kumar, A
Abstract: The present study deals with the analysis of various parameters in view of reliability for a manufacturing plant namely rice manufacturing plant, for considered conditions as well as availability during the season for the regenerating Markov model. The Laplace transformation has been used to simplify and for the explicit expressions of Availability, Reliability, MTTF. The numerical illustrations have been carried out for the data available in the literature. The profit analysis, sensitivity analysis carried out for the considered model.